2011
DOI: 10.1007/s12272-011-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Interference of alpha-synuclein with cAMP/PKA-dependent CREB signaling for tyrosine hydroxylase gene expression in SK-N-BE(2)C cells

Abstract: Alpha-synuclein (α-SYN) is a small and highly conserved presynaptic protein that is implicated in both normal brain function and the pathogenesis of neurodegenerative diseases. Although the physiological function of α-SYN has not been fully evaluated, several lines of evidence suggest that it plays an important role in the regulation of dopamine homeostasis in the brain. Early studies have demonstrated that interaction of α-SYN and tyrosine hydroxylase (TH), a rate-limiting enzyme in dopamine synthesis, is fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…CREB binds DNA sequences with cAMP response elements (CRE), which are present in the promoter of many genes, including tyrosine hydroxylase (TH) and synapsin I [19], [20]. Studies from our laboratory and other groups have previously reported decreased TH mRNA levels in HPRT-deficient cells [4], [8].…”
Section: Resultsmentioning
confidence: 99%
“…CREB binds DNA sequences with cAMP response elements (CRE), which are present in the promoter of many genes, including tyrosine hydroxylase (TH) and synapsin I [19], [20]. Studies from our laboratory and other groups have previously reported decreased TH mRNA levels in HPRT-deficient cells [4], [8].…”
Section: Resultsmentioning
confidence: 99%
“…The cAMP and Protein kinase A (PKA) signaling system may be affected at more levels by interactions with catalytic subunit beta, regulatory subunit type 2, as well as scaffolding A-kinase anchor protein 5. Such interactions may be involved in the αSN dependent attenuation of cAMP dependent TH gene expression in cells [ 69 ]. Additionally, we identified Protein kinase C epsilon, calcium/calmodulin-dependent protein kinase type 2, alpha subunit and creatine kinase thus linking αSN sensitive targets to phospholipase C and its substrate diacylglycerol, calcium regulation and bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…ASYN accumulation was found to up-regulate caveolin-1 and to down regulate several signaling pathways, upstream of cyclic adenosine monophosphate (cAMP) response element binding protein (CREB), such as extracellular signal regulated protein kinase (ERK), protein kinase C (PKC) [286,287], nuclear factor kappa B (NF-kB) [248,288] and glycogen synthase kinase 3b (GSK3b) [260]. Consequently, downregulation of CREB leads to impairment of its downstream targets, namely Bcl-2 [260] and brain-derived neurotrophic factor (BDNF) expression [289], which impairs tyrosine hydroxylase (TH) expression [290]. However, nuclear ASYN also downregulates expression of the nuclear receptor, Nurr1, and its downstream target, GDNF receptor, Ret.…”
Section: Asyn and Transcriptional Deregulationmentioning
confidence: 99%